Auditoría de gestión a la dirección administrativa de la Universidad Técnica de Cotopaxi, periodo 2022. - Quimbita Andrade, Carolina Mireya (2024)
This project was approved out with the objective of carrying out a Management Audit of the Administrative Management of the Technical University of Cotopaxi, period 2022. The quantitative approach was applied, since this direction allowed identifying specific factors of the organizational culture that influence the compliance with the goals and planned activities in the analyzed direction; On the other hand, using key performance indicators, a more precise and objective measurement of efficiency, effectiveness and economy was carried out. The type of research was bibliographic and field; given that, through a detailed review of the literature, the development of the Management Audit was theoretically based; and on the other hand, information was collected in the institution's facilities. The population was made up of the four officials of the department under study and the related areas. The results of the audit show 12 significant findings, which show deficiencies in the internal control of the Administrative Directorate and in compliance with the objectives, goals and activities of the Strategic Institutional Development Plan (PEDI). When applying the management indicators, an unfavorable gap of 29.82% was determined in relation to compliance with improvement plans; 21.05% in satisfaction with the organizational climate and appropriation of the organizational culture. Regarding the impacts of the project, it will contribute to operational efficiency, with the identification of shortcomings and the issuance of recommendations, it will contribute to the optimization of institutional resources.